A Theological and Ethical Perspective on Imposed Death - Anen, Bruno Ikun; Salurante, Tony (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This paper examines euthanasia from ethical, theological, legal, and human rights perspectives, focusing specifically on the Christian faith. Euthanasia, defined as the intentional termination of life to avoid physical suffering, raises significant moral and legal dilemmas. This study applies a qualitative method through literature review to explore expert opinions, Indonesian legal provisions, and theological foundations based on the Bible. The findings indicate that euthanasia contradicts the core principles of Christian ethics, Indonesian positive law, and human rights values that uphold the right to life. From a Christian worldview, life is a divine gift and should not be ended by human will. Suffering is understood as part of a spiritual journey that carries redemptive meaning. Furthermore, euthanasia presents complex implications not only for the individual undergoing the act but also for families, religious communities, and healthcare professionals. In Christian ethics, life and death are matters of divine sovereignty, and human agency in ending life is considered a violation of God's authority. The legal stance in Indonesia, as reflected in national laws and regulations, clearly prohibits any form of euthanasia, emphasizing the protection of human life as a constitutional right. From a human rights viewpoint, although autonomy is important, it must be balanced with the principle of preserving life. This study suggests that interdisciplinary dialogue involving theology, law, bioethics, and pastoral care is urgently needed to build awareness and offer compassionate responses to end-of-life issues. Churches, educators, and policymakers are encouraged to develop ethical guidelines and pastoral counseling approaches rooted in biblical truth and legal integrity. A wise and faithful response to the problem of euthanasia requires not only empathy but also a clear commitment to uphold the sanctity of life.